Assessing the risk of an investment project using an improved TOPSIS method. Issue 16 (19th September 2020) - Song, Yan; Li, Xinyun; Li, Yi; Hong, Xianpei
ABSTRACT: In this paper, we propose an improved TOPSIS evaluation model based on coordinated development. We improve the TOPSIS evaluation model by taking two indicators as examples to deduce the coordination degree between the indicators, based on spatial analytic geometry. Finally, we use a case study to validate the improved model. The results show that the improved model considers not only the weighted distance from the decision-making scheme to the ideal scheme and the negative ideal scheme, but also the coordination information of the multiple indicators, which has a certain theoretical value for multi-attribute decision-making problems.